Fetomaternal outcome among women with mitral stenosis after balloon mitral valvotomy. Issue 2 (1st March 2013) - Jain, Shuchi; Maiti, Tapan K.; Jain, Madhu
Abstract: Objective: To compare pregnancy outcomes among patients with non‐operated mitral stenosis and those who had balloon mitral valvotomy before pregnancy. Methods: In a study at a tertiary‐care referral hospital in Kolkata, India, 48 women with mitral stenosis who delivered between July 2007 and June 2008 were separated into 2 groups according to whether they had cardiac surgery before pregnancy. Eighteen women in the test group had balloon mitral valvotomy before pregnancy, whereas 30 women in the control group had no cardiac surgery. Fetomaternal outcomes were compared between the 2 groups. Results: In the control group, significantly more patients had palpitations ( P = 0.032) and severe dyspnea ( P = 0.017) than in the test group. The incidence of preterm labor in the test group (1/18) was lower than that in the control group (10/30) ( P = 0.035). However, the groups did not differ in mode of delivery, mean birth weight, or neonatal complications. Conclusion: Balloon mitral valvotomy improved maternal symptoms and should be done to prevent maternal morbidity and to reduce the incidence and complications of preterm labor.